Bounded choices: The problematisation of longterm care for people ageing with an intellectual disability in rural communities. (April 2017) - Bryant, Lia; Garnham, Bridget
Abstract: The increasing longevity of people with an intellectual disability and concurrent ageing with their older parental carers is generating a problematisation of longterm social care in the community. In rural communities this problematisation is complicated by spacial distribution and paucity of specialist disability and aged care services to cater to the emerging needs of these families. In-depth interviews with six families in rural South Australia were conducted to explore their experiences of caring in the community and future post-parental care plan for their son/daughter with an intellectual disability. The data reveal how the gendered nature of care installs moral responsibility for care through maternal subjectivity and problematizes relinquishing that care. The relinquishing of care was also problematised by a delimited discourse on care transition with a foundation in uncertain futures and bounded choices for longterm post-parental care. Powerful normative constructions of the 'good mother' are therefore at the heart of the 'carescape' for intellectual disability and shape intersubjective relations between mothers and their sons/daughters, neoliberal community care policy and practices and emotions associated with caring. The ethic of care normalised in the context of this carescape legitimates the State's limited provision of statutory services and supports for carers and people with disabilities. However, the increasing life-expectancy of people with intellectual disability and the age-related needs of their parental caregivers is problematizing this social service lacuna. The absence of clearly demarcated and suitable pathways for future care transition is an everyday lived uncertainty for older rural carers, subject to the agency of others and a concern that their son/daughter will enter into less desirable forms of care. Delimited agency and opportunity for those who give and receive care requires problematisation of the political, cultural and moral discourses through which longterm social care in the community is constituted.